OTORITAS POLITIK DALAM KODIFIKASI MUSHAF PADA MASA KHULAFĀ’ AL-RĀSYIDĪN - ANSHORI, MUHAMMAD (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
This paper seeks to explore the history of the study of codification of manuscripts which still remains problematic. Even some Muslim thinkers doubt the authenticity of the manuscripts circulating now, or commonly referred to as Mushaf ?U?m?ni. In Islamic history, the Qur'an at the time of the Prophet Muhammad was not codified as it is now. At that time, the diversity of reading methods (qir?'ah) was so rich that many friends had their own manuscripts. But in the time of ?U?m?n, the Mushaf only had one version because the other Manuscripts were  ?destroyed". Even many Mushaf were burned at that time, so some friends (campanions/?a??bah) did not accept this. This will not happen without anyone behind it, and certainly has to do with the caliph's political authority at that time as the holder of power. Then why did the time of khulaf? 'al-r?syid?n united the mushaf? What is the reason for the caliph of the early days of Islam to united the Mushaf and burned the other manuscripts? With a historical approach and analytical-critical method, this paper seeks to examine in depth the background or motives for the union of Mushaf and the burning of other best manuscripts. In addition, this paper will also briefly described some of the best-known Mushaf in the history of the Qur'an. They are ?Al? bin Ab? ??lib (d. 40 H), Ibn Mas'?d (d. 32 H), and Ubay bin Ka'ab (d. 21/22 H).